Barley Yield Response to Nitrogen Application under Different Weather Conditions - Tanaka, Ryo; Nakano, Hiroshi (Scientific Reports, 2019)
Barley, one of the most important crops worldwide, will be exposed to high air temperatures as a result of global warming. Since global warming is projected to progress with annual fluctuations, weather-adaptive cultivation techniques are needed in the area of barley production. This study aimed to determine the effect of nitrogen (N) application rate at heading on the grain yield of barley grown under different weather conditions based on two years of field experiments. Grain yield increased markedly with increasing N application rate in the 2017–2018 cropping season but not in the 2016–2017 cropping season. In contrast, late-emerging tillers clearly increased with increasing N application rate in the 2016–2017 cropping season but not in the 2017–2018 cropping season. Plants grown in the 2016–2017 cropping season produced relatively few grains due to the short period of tillering as a results of high air temperatures compared with those grown in the 2017–2018 crop season. Thus, in the 2016–2017 cropping season, N application could be used for the production of late-emerging tillers as a consequence of the limited sink capacity, whereas, in the 2017–2018 cropping season, it could be used effectively to increase grain yield.